The Editorial Discussion about the International Relations Research (Czech Journal of International Relations, 1967)
In past issues, our magazine has brought several discussion contributions to the issue research on international relations. They were written by well-known UMPE workers, who conduct research into international relations using a mostly historical-political method. In the past years the sociological approach got ahead to individual scientific disciplines. In today's world, sociology has also penetrated into the study of international relations and a council of schools and theories was created.To discuss all these questions and further development of the methodological side of the research of international interest, the editors invited several experts on December 13, 1966 toabove all, they assessed the possibilities of a sociological approach to the study of international relations. Sociologists Assoc. M. Soukup and doc. K. Kára from the CSAV Institute of Sociology, doc. R. Selucký, economist and dramaturg Cs. state film, and doc. from UMPE took part in it. M. Nikl, dr. Placek, doc. V. Sojak, dr. J. Stepanovsky and edited by dr. J. Sedivý, who moderated the discussion, and M. Kovárová.The discussion showed that the sociology of international relations is still in Czechoslovakia in the beginning, it is difficult to decide in which direction to focus the research, which topics to choose for their processed has enriched both social sciences and practical politics, what methods apply, take over and create.